STAGES OF DENTAL PROSTHETICS WITH VENEERS - Хожимуродов Бурхон Равшанович; Нарзиева Нигора (American Journals, 2023)
Healthy and beautiful teeth are the most important element of human attractiveness. Cosmetic issues are the focus of dental clinics. Veneers and laminates made of ceramic and composite materials have become very popular as a means of quickly changing the appearance. The rapid development of materials science in dentistry and new methods of aesthetic dentistry made it possible to restore and correct the color, shape and position of teeth, recreate harmonious bites and Smile. Bonding systems and composite materials allow you to eliminate aesthetic obstacles without the use of traditional orthopedic methods of treatment. Methods of aesthetic restoration of vestibular surfaces of teeth with the help of composite veneers are widely used. This type of aesthetic work involves not only the elimination of defects, but also a detailed reproduction of anatomical shapes, optical effects and individual characteristics.